2018
DOI: 10.1111/joa.12800
|View full text |Cite
|
Sign up to set email alerts
|

HIF1α protein and mRNA expression as a new marker for post mortem interval estimation in human gingival tissue

Abstract: Estimating the post mortem interval (PMI) is still a crucial step in Forensic Pathology. Although several methods are available for assessing the PMI, a precise estimation is still quite unreliable and can be inaccurate. The present study aimed to investigate the immunohistochemical distribution and mRNA expression of hypoxia inducible factor (HIF‐1α) in post mortem gingival tissues to establish a correlation between the presence of HIF‐1α and the time since death, with the final goal of achieving a more accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
2
18
1
5
Order By: Relevance
“…The lack of a correlation between HIF-1α mRNA expression and the postmortem interval (PMI) is in contrast to the study of Fais et al [ 39 ]. In the cases of PMIs between 1 and 5 days, they reported an increase in HIF-1α mRNA expression in gingival tissue, but when the PMI was longer than 5 days, the HIF-1α expression decreased and was no longer detectable at a PMI of 10 days.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The lack of a correlation between HIF-1α mRNA expression and the postmortem interval (PMI) is in contrast to the study of Fais et al [ 39 ]. In the cases of PMIs between 1 and 5 days, they reported an increase in HIF-1α mRNA expression in gingival tissue, but when the PMI was longer than 5 days, the HIF-1α expression decreased and was no longer detectable at a PMI of 10 days.…”
Section: Discussioncontrasting
confidence: 58%
“…In the cases of PMIs between 1 and 5 days, they reported an increase in HIF-1α mRNA expression in gingival tissue, but when the PMI was longer than 5 days, the HIF-1α expression decreased and was no longer detectable at a PMI of 10 days. Vennemann and Koppelkamm [ 40 ] stated that the endogenous reference gene GAPDH, which was used by Fais et al [ 39 ], is not a stable reference gene, because it is influenced by hypoxia. The application of three stable reference genes may explain the different results of the present study, which are in accordance with studies of Zhu et al [ 41 ] and Zhao et al [ 42 ], indicating that HIF-1α is a good marker of hypoxia, because its expression is not influenced by gender, age, and PMI.…”
Section: Discussionmentioning
confidence: 99%
“…Regression analysis results revealed no significant relationship between HIF -1α and PMI within the 168 h after death both in control and experimental. In our present study, we found that the postmortem changes of HIF-1α was consistent with previous study that HIF-1α expression was gradually decreased 4-5 days after death 28 ; However, HIF-1α protein expression as a new marker for PMI estimation in human gingival tissue was confirmed in previous study and the results of the study suggested HIF1α is a promising biomarker for distinguishing deaths that have occurred within 1 week from those that occurred more than 1 week ago; So that much more long-term observation of HIF-1α expression in our further study will help us to explain the difference between previous study and our current study.…”
Section: Association Between Tn-t Vegf Hif-1α Vegf/tn-t Hif-1α/tnsupporting
confidence: 93%
“…Our present study indicated that postmortem changes of HIF-1α expression was stable both in control and experimental within 72 h after death. The HIF-1α levels in experimental group was decreased 48 h after death and the differences was found in the group of 72 h compared with control; which was supported by the foundings of Fais P et al that HIF-1α expression was gradually decreased in samples collected 4-5 days after death and it was not detected 8-9 days after death 28 . So that the postmortem diagnostic role of HIF-1α need more long-term observation over 168 h after death to more accurate conclusions.…”
Section: Postmortem Changes In Tn-t Vegf Hif-1α Vegf/tn-t Hif-1α/supporting
confidence: 68%
“…Se identificaron estudios entre los años 1994 y 2019, 5 de los cuales han sido publicados en los últimos 3 años. Es destacable que 3 de esos 5 artículos han focalizado su investigación en la aplicación de métodos IHQs en tejidos obtenidos de la cavidad oral (Mazzotti et al;Fais et al, 2018;Charan Gowda et al).…”
Section: Resultsunclassified